Electrodeposition of copper-lead alloys from a methanesulfonic acid electrolyte / Balachandar a/l Subramaniyan - Subramaniyan, Balachandar (2013)
The electrodeposition of Copper-lead alloys on steel sheet cathodes has been studied by electrodeposited from baths containing aqueous mixtures of lead (II) acetate trihydrate, copper (II) acetate monohydrate and methane sulfonic acid (MSA) with varying current densities at room temperature. This was enabled by using a Cu:Pb ratio of 1:3 in the electrolyte. The composition of copper-lead alloys was influenced by metal ion ratio in the bath. This study focused on the process of electrodeposition of copper-lead alloy (lead content in the deposit up to 20%) from methane sulfonic acid electrolyte. The anode material used was graphite. Methanesulfonic acid is an alternative electrolyte system which could replace others acid in practical. The results were consistent with the behaviour of a regular plating system with copper being the preferentially depositable metal. It has been shown that the lead (the less noble metal) content in the deposits increases at an increase in current density in the electrolyte. The properties (surface microstructure, phase composition and crystallite size) of the electrodeposits were characterised by X-ray diffraction (XRD), scanning electron microscope (SEM) and energy-dispersive X-ray (EDX). The results showed that the deposits consist of a mixture of fine crystals of the two metals and the morphology of the deposits is mainly controlled by the composition of the deposit. It is confirmed that there is a formation obtained in MSA were exhibiting fine and rough, quietly uniformity, crystalline and moderately adherence on the cathode surface. According to the XRD result, the crystal structure of the copper-lead alloy coatings is face-centred cubic (FCC) structure. By increasing the deposition current densities decrease the copper content. The mass electrodeposition increases gradually when deposition current density is increased. At low deposition current density, low value of the current efficiency may be due to the evaluation of the hydrogen at the cathode. The values of the current efficiency obtained are in the range of 86-99 %. Detailed electrochemical studies with the help of cyclic voltammetry helped in understanding the role played by these singles and mixture Cu-Pb alloy from MSA baths onto steel electrode during deposition.